PREVALENCE OF ASYMPTOMATIC LEISHMANIA INFECTION IN PEOPLE LIVING WITH HIV AND PROGRESSION TO SYMPTOMATIC VISCERAL LEISHMANIASIS IN BIHAR, INDIA - R. Mahajan; S. Owen; S. Kumar; S. Kazmi; K. Pandey; N. Verma; V. Kumar; A. Harshana; E. Lasry; L. Moretó-Planas; E. Adams; S. Burza (International Journal of Infectious Diseases, 2023)
Intro: People living with HIV (PLHIV) have an increased risk of developing visceral leishmaniasis (VL) and poor outcomes compared to HIV-negative individuals. Here, we aim to establish the prevalence and determinants of asymptomatic Leishmania infection (ALI) and the rate and risk factors for progression of ALI to VL in a cohort of PLHIV in Bihar, India. Methods: We conducted a cross-sectional survey of PLHIV ≥18 years of age with no history or current diagnosis of VL or PKDL at anti-retroviral therapy centres within VL endemic districts of Bihar. ALI was defined as a positive rK39 ELISA, rK39 RDT, and/or qPCR. Additionally, the urinary Leishmania antigen ELISA was evaluated. The ALI and non-ALI cohorts were followed up every three months for 18 months in person and by telephone, respectively. Determinants for ALI were established using logistic regression model. Findings: A total of 1,296 PLHIV enrolled in HIV care, 694 (53.6%) of whom were female and a median age of 39 years (IQR 33–46), were included in the analysis. The baseline prevalence of ALI was 7.4% (n=96). All 96 individuals were positive by rK39 ELISA, while 0.5% (n=6) and 0.4% (n=5) were positive by qPCR and rK39 RDT, respectively. Risk factors for ALI were CD4 counts <100 (OR 3.1; 95%CI 1.2–7.6) and CD4 counts 100-199 (OR=2.1; 95% CI: 1.1-4.0) compared to CD4 counts ≥300, and a household size ≥5 (OR=1.9; 95%CI: 1.1-3.1).Within the ALI cohort, four (3.7%) participants developed VL, compared to no progression in the non-ALI cohort. Mortality rates were higher in ALI compared to non-ALI (OR =2.7; 95% CI: 1.1-6.1). Conclusion: The prevalence of ALI in PLHIV in VL endemic villages in Bihar was relatively high. However, the progression rate from ALI to VL in PLHIV was low. Patients with low CD4 counts and larger household size were at higher risk of ALI.